Cyclic regeneration and up-concentration for nitrate recovery from wastewater via in situ NaNO3 generation under saline, fully autotrophic nitrification conditions - Molin Lian; Zihang Ma; Guang Chen; Siqi Yu; Qing Xia; Bingjie Lin; Xiangdong Xu; Rui Tang; Zhen Zhou (Bioresource Technology, 2026)

Highly elastic and multifunctional polyimide/Ti3C2TX Mxene composite aerogels for thermal insulation, flame retardancy and oil absorption - Fanshen Meng; Dongliang Zhang; Zihang Zhang; Yu Lin (Journal of Environmental Chemical Engineering, 2026)

Synergistic regulation of cadmium tolerance by a 2 C protein phosphatase and nano molybdenum by modulating cellular structure, metal transport, and redox homeostasis in polyploid rice - Muhammad Qasim Shahid; Zihang Lin; Lixia Sun; Zhen Li; Muhammad Farooq; Fozia Ghouri (Journal of Hazardous Materials, 2026)

Molecular characterization and expression analysis of three complement genes: C4B, C6 and C7 in Mastacembelus armatus under Aeromonas veronii infection - Kaifeng Wang; Ziyan Deng; Shengyue Lin; Min Zhang; Guojun Cai; Zihang Xie; Chong Han; Qiang Li (Fish & Shellfish Immunology, 2026)

YAP/TEAD complex restricts H3K27ac deposition to suppress testosterone synthesis in adult Leydig cells - Zeyu Lin; Shanshan Luo; Mei Zheng; Zihang Lin; Lvjing Luo; Dini Zhang; Xiuli Lian; Xuanyi Wang; Shie Wang; Jiandong Sun (Histochemistry and Cell Biology, 2026)

Rice 2C protein phosphatase, OsNY1, and magnesium oxide positively regulate arsenic tolerance by root cells reinforcement, metals detoxification, and protein phosphorylation - Zihang Lin; Lixia Sun; Weiwei Xia; Zhen Li; Fozia Ghouri; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2026)

Characterization of transglutaminase-crosslinked black bean-whey dual protein complexes for constructing oleogel-based emulsions and application in low-fat salad dressings - Fengjuan Chen; Mingyue Shen; Jieqiong Lin; Zihang Fu; Jianhua Xie (Food Chemistry, 2026)

Cellulose nanofibers regulate nonlinear rheological behavior and structural stability of soy protein isolate emulsion gels for 3D printing - Jieqiong Lin; Jun Yang; Xiaohua Liu; Fenjuan Chen; Lixin Guo; Zihang Fu; Jianhua Xie (Food Hydrocolloids, 2026)

Reshaping heavy metal pathways: A long-term field study on emissions and partitioning in municipal solid waste (MSW) incineration before and after MSW classification - Junxiao Wei; Liwei Sun; Zihang Ding; Wanjia Lin; Huan Li; Jianguo Liu (Journal of Hazardous Materials, 2026)

Anisotropic delignified wood/Ti3C2Tx MXene aerogel composite for stable and efficient solar desalination - Zihang Zhang; Ruina Zheng; Shenyu Peng; Siqi Ling; Yu Lin (Journal of Environmental Chemical Engineering, 2026)

Portable smartphone-assisted fluorescence platform based on dual-excitation nitrogen-doped carbon dots for simultaneous detection of chlorogenic acid and tinidazole - Junyuan Shi; Zihang Yin; Dejin Lin; Dingfeng Wang; Siting Peng; Wendi Xiao; Houwen Hu; Jiong Cheng; Da Chen (Analytica Chimica Acta, 2026)

Anomaly detection for LNG storage tanks with limited sensor data using WGAN-CADA and multi-branch probabilistic autoencoder - Yang Yu; Jiandong Ma; Jianxing Yu; Zihang Jin; Hanxu Tian; Yuheng Yang; Lin Song (Process Safety and Environmental Protection, 2026)

Characterization, expression and evolution analysis of NLRC3 , NLRC5 and NLRX1 in Mastacembelus armatus under Aeromonas veronii infection - Shengyue Lin; Kaifeng Wang; Weijian Chen; Ziyan Deng; Guojun Cai; Min Zhang; Zihang Xie; Weibin Li; Chong Han; Qiang Li (Journal of Fish Biology, 2026)
NOD‐like receptors (NLRs) serve as crucial innate immune sensors in multicellular organisms, recognizing diverse pathogen‐associated components and regulating immune responses such as nuclear factor kappa B (NF‐κB) signalling and inflammatory pathways. To elucidate the roles of NLRC3 , NLRC5 and NLRX1 in the innate immunity of the Mastacembelus armatus , this study first characterized these genes and examined their response to Aeromonas veronii infection. We identified the three NLR genes from the M. armatus transcriptome and analysed their evolutionary relationships through domain architecture and maximum likelihood (ML) phylogenetic reconstruction. All three NLR proteins contained conserved NACHT and leucine‐rich repeat (LRR) domains, and ML phylogenetic analysis grouped M. armatus with other Synbranchiformes and Perciformes, consistent with established taxonomy. Tissue expression profiling in healthy fish revealed constitutive expression of all three genes across nine examined tissues, with significantly higher levels in gills, suggesting their involvement in frontline mucosal immunity. Temporal expression analysis in spleen, liver and kidney following A. veronii challenge showed distinct organ‐specific patterns: although all three genes were downregulated in the liver, they were significantly upregulated in spleen and kidney, indicating these as primary sites for NLR‐mediated immune responses in M. armatus . Selection pressure analysis using CodeML identified widespread purifying selection across teleost NLRs, alongside multiple positively selected sites in NLRC5 (7 sites in site model, 5 in branch‐site model) and NLRX1 (2 sites in site model, 22 in branch‐site model). These findings provide fundamental insights into NLR‐mediated immunity in M. armatus and contribute to understanding the evolution and function of NLR genes in teleosts.

Experimental Study on Hydrodynamic Responses of Multi-Body Floating Systems Under Combined Wind, Wave, and Current Loads - Lin Song; Jianxing Yu; Hanxu Tian; Ruilong Gao; Jiandong Ma; Zihang Jin (Journal of Marine Science and Engineering, 2026)
As the development of the ocean extends to the deep and open seas, the application of multi-hull floating systems is becoming increasingly widespread, covering offshore oil and gas transfer and material replenishment operations. In multi-body floating systems, the hydrodynamic interactions between adjacent floating bodies significantly affect the overall motion response and load distribution. However, there is currently a lack of systematic experimental research on systems involving three or more units under the combined action of wind, waves, and currents. This study presents a 1:50 scale model experiment on a five-body offshore replenishment station, comprising a central transfer platform and four surrounding vessels. Absolute six-degree-of-freedom motions and relative displacements between the transfer platform and neighboring vessels were measured. The results indicate distinct differences among the units. The peripheral vessels have greater horizontal and yaw motions, while the central units are more restricted. The relative motions are substantially increased for beam and oblique wave conditions, implying increased interaction effects in the gaps between neighboring bodies. Moreover, the combined oblique environmental loading and asymmetric mooring stiffness result in increased global drift and yaw motions. These findings provide benchmark data for numerical validation and practical guidance for the design and operation of multi-body floating systems.

Polyploidy and zinc nanoparticles enhanced cadmium tolerance by regulating antioxidants and transport proteins - Jingwen Liu; Fozia Ghouri; Lixia Sun; Zihang Lin; Minghui Zhong; Muhammad Farooq; Muhammad Qasim Shahid (Plant Cell Reports, 2026)

Unlocking biochar's carbonyl group: Fe-Mn oxide synergy enables high-efficiency As(III) immobilization via non-radical oxidation - Zihang Cheng; Yilin Wu; Ruiqi Du; Mingming Lin; Jingzi Beiyuan; Juan Liu; Peng Liu; Bowen Li; Xueding Jiang; Hailong Wang (Journal of Environmental Management, 2025)

Mechanical performance analysis of a dual-spar floating wind farm considering different shared mooring systems - Xiang Lin; Jingrui Zhao; Wenzhou Liang; Zhishuai Liu; Zihang Yu (Frontiers in Marine Science, 2025)
Introduction In recent years, as floating wind turbines advance into deeper waters, mooring systems represent a growing share of the overall investment. Shared mooring can simplify mooring arrangements and improve the economic efficiency of wind farms. However, it also increases the dynamic complexity of multi-turbine systems, introducing risks of high tension levels and snap events under extreme conditions, which must be addressed during the mooring design phase. Methods This study compares the coupled dynamic responses of three typical shared mooring systems: pure steel cable, polyester rope with a clump weight, and chain with a buoy. Mooring design is based on the catenary equation, and time-domain simulations are conducted using OrcaFlex to analyze the impact of various shared mooring configurations on the hydrodynamics and mooring performance of wind turbine systems. Results The results show that, compared to the baseline configuration, the taut single-weighted configuration is more effective in reducing the fluctuation of mooring tension under extreme conditions, thus avoiding the occurrence of snap events. As the clump weight mass increases, the surge motion of the platform is effectively suppressed, but the heave and pitch motions may become more pronounced. Therefore, a balance must be struck between the clump weight mass, platform motion, and mooring tension to achieve optimal overall performance. The catenary with buoy configuration shows similar results to the taut single-weighted configuration; however, the maximum tension of shared mooring may occur at the buoy connection. Additionally, excessive net buoyancy can exacerbate the dynamic characteristics of the buoy and raise the risk of collision between the buoy and passing vessels. This study contributes to a deeper understanding of shared mooring systems and provides valuable guidance for their design.

Trps1 targets Scarb1 to regulate cholesterol acquisition in mouse Leydig cells - Xiuli Lian; Zihang Lin; Weitao Hu; Zhangting Chen; Shanshan Luo; Shumin Liao; Yue Liu; Shie Wang; Jiandong Sun (Reproductive Biology, 2025)

Effect of stepwise cooking on the water-retention capacity and protein denaturation degree of chicken breast - Zihang Li; Qianyi He; Jiaxin Lai; Jie Lin; Shaozong Wu; Zonglin Guo; Hua Zheng (International Journal of Gastronomy and Food Science, 2024)

In vitro digestion mimicking conditions in adults and elderly reveals digestive characteristics of pork from different cooking ways - Xiangyue Cao; Fan Zhao; Ziyi Lin; Xiaomei Sun; Xianming Zeng; Haoxi Liu; Yutong Li; Zihang Yuan; Yuan Su; Chong Wang; Guanghong Zhou (Food Research International, 2024)

A novel BACG inverse reliability algorithm for efficient and robust reliability-based topology optimization of marine structures - Yupeng Cui; Baolei Zhang; Yang Yu; Siyuan Cheng; Mingxiu Wei; Zihang Jin; Lin Song (Ocean Engineering, 2024)

Microbiological mechanisms of sludge property variations under long-term landfill: From micro-omics perspective - Yunxin Xing; Ying An; Lifeng Lin; Peng Peng; Xiaolu Gong; Weijie Hu; Yuqing Ren; Zihang Ma; Jiafu Xi; Jing Cao; Ziyang Lou; Zhen Zhou (Chemical Engineering Journal, 2024)

Does mangrove leave falling dominate the bury of polycyclic aromatic hydrocarbons in the mangrove of China? - Yingying Qian; Meiru Liang; Zixing Zhao; Zihang Zhang; Minggang Cai; Yan Lin (Marine Environmental Research, 2024)

Enhanced management and antifouling performance of a novel NiFe-LDH@MnO2/PVDF hybrid membrane for efficient oily wastewater treatment - Kai Fan; Ning Kong; Jing Ma; Hongjun Lin; Chuanyang Gao; Jinshen Lei; Zihang Zeng; Jun Hu; Juncheng Qi; Liguo Shen (Journal of Environmental Management, 2024)

Determination of key factors affecting biofilm formation on the aged Poly(ethylene terephthalate) during anaerobic digestion - Chao Zhang; Zihang Dong; Qindong Chen; Yeqi Lin; Yutong Zhou; Qiyong Xu (Chemosphere, 2023)

Nitrogen removal from dewatering liquid of landfill sludge by partial nitrification and denitrification - Zihang Ma; Lifeng Lin; Jiafu Xi; Xiaolu Gong; Jianqiao Wang; Peng Peng; Ying An; Weijie Hu; Jing Cao; Zhichao Wu; Zhen Zhou (Bioresource Technology, 2023)

Uncertainty propagation of turbulence parameters for typhoon and Non-typhoon winds in buffeting analysis of Long-span bridges - Zihang Liu; Genshen Fang; Lin Zhao; Yaojun Ge (Engineering Structures, 2023)

Neoproterozoic Diamictite of the Luoquan Formation from the North China Block and Their Implications - Peishan Sui; Weidong Sun; Nan Han; Lei Wang; Shiwen Xie; Zihang Huang; Xiaohong Wang; Hongmei Gong; Jin Liu; Jinyan Lin; Yuanyuan Xiao (Journal of Earth Science, 2023)

Combined Application of Calcium-Magnesium Phosphate Fertilizer with Soluble Phosphorus Improves Maize Growth in a Calcareous Soil - Zihang Yang; Wenli Zhou; Baoru Sun; Zed Rengel; Gu Feng; Lin Zhang (Journal of Soil Science and Plant Nutrition, 2023)